Cryopreserved stem cell products containing dimethyl sulfoxide lead to activation of the coagulation system without any impact on engraftment. Issue 6 (4th December 2013) - Holbro, Andreas; Graf, Lukas; Topalidou, Maria; Bucher, Christoph; Passweg, Jakob R.; Tsakiris, Dimitrios A.
<x xml:space="preserve">Abstract</x> Background Dimethyl sulfoxide (DMSO) is extensively used as a cryoprotectant in stem cell preservation. Little is known on direct hemostatic changes in recipients of hematopoietic stem cell transplantation (HSCT), immediately after DMSO administration. The objectives of the current study were to measure hemostatic changes during HSCT. Study Design and Methods In this prospective analysis, changes in plasma biomarkers, platelets (PLTs), or endothelial cells (D‐dimers, thrombin–antithrombin complex [TAT], microparticle activity as thrombin‐generation potential [MPA], whole blood aggregation, von Willebrand factor) were measured before and immediately after HSCT. Furthermore, associations with clinical complications were recorded. Results A total of 54 patients were included in the study. Mean MPA and TAT increased significantly immediately after HSCT, returning to baseline the day after the procedure (p < 0.01). No significant differences in engraftment for neutrophils and PLTs were found in patients presenting a high increase of TAT or MPA compared with those presenting with a smaller increase. Patients with a high increase in TAT and MPA had received a greater number of total mononucleated cells (p < 0.001) and higher transplant volumes (p = 0.002). Conclusions Infusion of stem cells containing DMSO reversibly activated coagulation, measured as thrombin generation. This finding was not associated with acute adverse events and did not influence engraftment. Further studies are needed to compare variable DMSO concentrations as well as DMSO‐free products, to better address the influence of DMSO on hemostasis.